The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/nau.24546
|View full text |Cite
|
Sign up to set email alerts
|

Defining nocturnal polyuria in women

Abstract: Aims: Nocturnal polyuria (NP) is defined by the International Continence Society (ICS) as "excessive production of urine during the main sleep period" and is one of the main causes of nocturia. The ICS recognized that "excessive" is not clearly defined and that this needs to be highlighted in both clinical and research settings. The aim of this study was to identify different definitions of NP and apply them to a population of women attending the Urogynaecology clinic. Methods: This was a retrospective study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
(64 reference statements)
2
4
0
Order By: Relevance
“…In this study, we did find a higher rate of nocturnal polyuria in the nocturia-BD group (Table 4 ), and this finding is in line with the concept of nocturnal polyuria as one of the main causes of nocturia 12 . Thus, this BD classification system seems to be a reasonable tool for classifying the nocturia-BD group in women with storage lower urinary tract symptoms.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we did find a higher rate of nocturnal polyuria in the nocturia-BD group (Table 4 ), and this finding is in line with the concept of nocturnal polyuria as one of the main causes of nocturia 12 . Thus, this BD classification system seems to be a reasonable tool for classifying the nocturia-BD group in women with storage lower urinary tract symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, the main medical treatments for OAB include antimuscarinics, beta 3-agonist, or combination therapy. Nonetheless, a total of 8.2% (179/2127) of OAB women were allocated into the nocturia-BD group (Table 1 ), and women in the nocturia-BD group may be better treated by desmopressin 12 , 13 , instead of antimuscarinics or beta-3 agonist. In addition, prolonged treatment was suggested to decrease retreatment in OAB women with small bladder capacity 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of women in EpiNP offers new insight into NP across the lifespan for women. Baines et al [29] compared NP prevalence using NPI and NUP90 definitions for women attending a urogynecology clinic and found that NP prevalence was much higher when using agedependent NPI thresholds (NPI >20% for those 65 yr and >33% for those >65 yr, with rates ranging from 58.4% to 77.5%, respectively). However, for NUP90 as a definition the prevalence was much lower at 17.9%, with no agedependent threshold used.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in 1,400 women found that prevalence of NP differed considerably, from 21.5%e77%, depending upon NP definition. 16 As such, a large cross-sectional, populationrepresentative study of both men and women (Epidemiology of Nocturnal Polyuria [EpiNP] Study) was conducted to assess the prevalence of NP in the U.S.; adjusted overall NP prevalence using NPI33 was 31.5% (men) and 38.5% (women), and was 23.8% (men) and 18.1% (women) using NUP90. 17 The main objective of this analysis was to compare bladder diary data parameters by NP definition (NPI33 and NUP90) to further evaluate the characteristics of NP definitions and examine potential sex-based differences.…”
mentioning
confidence: 99%
“…A recent study conducted in 1,400 women found that prevalence of NP differed considerably, from 21.5%–77%, depending upon NP definition. 16…”
mentioning
confidence: 99%